Salivary IgA as a potential biomarker in the evaluation of respiratory tract infection risk in athletes - Turner, S. E.; Loosemore, M.; Shah, A.; Kelleher, P.; Hull, J. H. (The Journal of Allergy and Clinical Immunology, 2020)
In recent years, there has been attention focused on the value of salivary IgA (sIgA) as a potential biomarker for the identification of athletes who may be at increased risk of developing respiratory tract infection (RTI). The utility of sIgA, in this context, is based on biological plausibility and several observational studies revealing an apparent association between sIgA and RTI susceptibility. The overall published evidence evaluating the value of sIgA in this context is however conflicting, and there is currently a lack of clear guidance as to whether this marker has a place in the health surveillance and care of athletes. In this review, we critically appraise the literature assessing the potential for sIgA to be used in this context, evaluating it against 4 key biomarker characteristics, including its (1) practicality, (2) reproducibility, (3) specificity/sensitivity, and (4) potential clinical impact and relevance. This process reveals that although there is an apparent association between respiratory illness and sIgA in many studies, with some promising results, overall there remains a paucity of evidence supporting its overall value in this context. Key deficiencies in the metrics employed to endorse a valid biomarker are apparent, including a lack of reproducibility and low specificity and sensitivity in the detection of RTI susceptibility. The review outlines these issues and makes future recommendations.